(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The research is significant because it identifies arbitration performance and its link to intelligent leadership and emotional management of handball referees in Iraq. The research problem was that there is a weakness in the level of performance of the referees caused by inefficiency of smart leadership and emotion management, or not using them in an appropriate manner and time, as recent directives of the Referees Committee and the Laws of the International Federation of the Game indicate the need to reduce the number of stops that occur during the match. In addition to decreasing penalties via effective leadership and the way of delivering the judgement with communicative skill between the referee and others, so that the referee regulates their emotions while remaining in control of his own. The purpose of this study was to construct a scale of smart leadership and emotional management in Iraqi handball referees and to identify the relationship between arbitrage performance, smart leadership, and emotional management in Iraqi handball referees. Correlations in measures of mediation performance, smart driving, and emotional management. The research community was determined by the handball referees in Iraq for the sports season (2022-2023), with 57 referees representing 13 governorates and 50 referees selected from the research community to build measures of smart leadership and emotional management. The standards and testing were applied to a sample consisting of 43 judgments from the research community. As for the most important conclusions, there was a very strong correlation between arbitral performances on the one hand as a dependent variable and smart leadership and emotion management as independent variables. To predict the arbitration performance in terms of smart leadership and emotion management among handball referees in Iraq, the curriculum of the Iraqi Central Handball Federation and the Central Referees Committee should include developmental courses related to the areas of smart leadership and emotional management, and conduct research and other similar studies on referees for other games in the sports field.